REVIEW ARTIKEL: ANALISIS pH, KONDUKTIVITAS, DAN OKSIGEN TERLARUT PADA AIR SERTA KADAR LOGAM BESI MENGGUNAKAN SPEKTROFOTOMETRI UV-VIS - Putri, Marlisa Roro; Yusuf, Bohari; Lianasari, Ika Yekti (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
A literature review on the analysis of conductivity, ph and Dissolved Oxygen parameters and the application of uv-vis spectrophotometry in measuring iron metal levels in water was conducted. This literature review reviewed several studies related to water quality analysis with several parameters and measurement of total iron levels. Commonly used parameters include pH, conductivity, Dissolved Oxygen (DO), and iron metal levels. Measurements are made with tools such as pH meters, conductivity meters, DO meters, and UV-Vis spectrophotometry for iron metal levels. The use of UV-Vis spectrophotometry as a detection method was chosen due to its accuracy in quantitative analysis and its ability to identify dissolved metal species non-destructively. The results showed significant variations in these parameters at various locations. Some of these parameters did not meet the recommended water quality standards. The iron metal concentration data obtained showed variations in values depending on the type of complexant used in each sample. The main factors of concern are heavy metal contamination, especially iron, as well as low Dissolved Oxygen levels. The importance of regular water quality monitoring and better management is emphasized to maintain environmental balance and public health. Keywords : Water quality, Dissolved oxygen, Conductivity, pH, Iron.